SEASONAL MONITORING OF THE INVASIVE SPECIES HALYOMORPHA HALYS Stal. ON DECORATIVE PLANTS IN THE CONDITIONS OF THE REPUBLIC OF MOLDOVA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii)
The brown marmorated stink bug Halyomorpha halys Stal is one of the most aggressive invasive insect species, posing a serious threat to agricultural crops and decorative plants in Europe and North America. Over the past five years, it has been actively spreading in the Republic of Moldova, causing damage to both agriculture and ornamental plantings. This study conducted seasonal monitoring of Halyomorpha halys on ornamental plants, focusing on visual inspections of plants such as lilac (Syringa spp.) and ailanthus (Ailanthus altissima Mill.), which are potential hosts for this species. Regular inspections of the plants revealed the presence of adults, nymphs, and egg masses, and tracked population dynamics throughout the growing season. On lilac, adults predominated from june to july, while from august to september, during the development of the third generation and seed maturation, there was an increase in nymph populations. On ailanthus, adults were dominant in the first ten days of august (up to 12 individuals per branch), whereas nymphs of all stages dominated during the second and third ten days of august. Keywords: Halyomorpha halys, marble bug, invasive species, ornamental plants, monitoring, adults, Republic of Moldova.